One child, two languages : a guide for early childhood educators of children learning English as a second language - Tabors, Patton O. (Baltimore, Md. : Paul H. Brookes Pub. Company, 2008)
The new edition of this accessible book for early childhood educators includes updated research and a greatly expanded chapter on assessment and highlights cultural diversity. It also includes a new tool for monitoring children's progress as they learn English as a second language. Updated from the first edition and written expressly for teachers, this highly readable resource moves beyond the basics of child development to describe the natural progression of second-language acquisition in young children. Teachers will learn how to create a supportive classroom environment for second-language learners with effective ways to measure progress, address individual differences, and work with parents while acknowledging the importance of children's home language and cultures.
Introduction -- Two portraits: Juliana and Byong-sun -- Getting started in a second language -- Speaking a second language -- Individual differences in second-language learning -- Using information, communication, and classroom organization to support second-language learning -- Using the curriculum to facilitate second-language and -literacy learning -- Working with parents of second-language learners -- Assessing the development of second-language learners -- Developing effective early childhood programs for second-language learners -- What to expect, how to help -- Appendix A: Parent questionnaire -- Appendix B: Observing children learning English (OCLE).
Includes bibliographical references (pages 203-209) and index.
Keywords: Second language acquisition